Successful Treatment of Chronic Venous Ulcers With a 1, 320-nm Endovenous Laser Combined With Other Minimally Invasive Venous Procedures. Issue 8 (August 2016) - Wysong, Ashley; Taylor, Brent R.; Graves, Michael; Mishra, Vineet; Gilbertson, Ryan; Greenway, Hubert T.; Housman, Leland
Abstract : BACKGROUND: Venous ulcers are very common with few curative treatment options. OBJECTIVE: To report the closure rate and clinical characteristics of active venous ulcers in a vein clinic using endovenous laser ablation (EVLA) with a 1, 320-nm laser. METHODS AND MATERIALS: A prospective database was kept consisting of patients with an active venous ulcer at the time of consultation in a single-practitioner academic vein clinic from March 2007 to May 2014. A database was maintained and charts were reviewed with attention to the length of time the patient reported having the ulcer, procedures performed, and time to ulcer healing. RESULTS: Thirty-one patients were identified at consultation with venous ulceration. One patient's ulcer was healed with conservative medical management before receiving treatment. The remaining 30 patients were treated with a combination of EVLA of the great and/or short saphenous veins, foam sclerotherapy of insufficient varicose and reticular veins, and phlebectomy as appropriate. Two patients were lost to follow up after partial treatment. Ulcer healing occurred in more than 93% (27/29) of patients with a median healing time of 55 days from the time of first treatment. The median follow-up time after treatment was 448 days. CONCLUSION: Endovenous laser ablation with a 1, 320-nm laser in combination with foam sclerotherapy and phlebectomy as appropriate is effective treatment of chronic venous ulcers and should be considered as a treatment option for patients with C6 venous insufficiency. To the authors' knowledge, this is the largest, prospective series of chronic venous ulcers treated with EVLA. Further randomized controlled studies are needed to confirm these findings.